Invasive aspergillus sinusitis with orbitocranial extension - Baeesa, Saleh; Bokhari, Rakan; Alghamdi, Khalid; Alem, Hisham; Al-Maghrabi, Jaudah; Madani, Tariq (Asian Journal of Neurosurgery, 2017)
Context: Invasive sinonasal aspergillosis is a silently progressive disease that, left untreated, may invade the adjacent intracranial and intra-orbital compartments incurring serious morbidity. Aim: To evaluate our results of a collaborative surgical management plans for patients with invasive sinonasal aspergillosis with orbitocranial extension. Setting and Design: Retrospective study. Materials and Methods: Between the years 2000 and 2012, 12 patients with Aspergillus sinusitis with orbitocranial extension were treated at our institution. Preoperative CT and MRI scans were done in all cases and cerebral angiography in two patients with subarachnoid hemorrhage (SAH). Surgical combined transcranial and endonasal approaches to the skull base were considered in all patients. Adjuvant antifungals were administered postoperatively with regular clinical and radiologic follow up. Results: All cases had a long history of headache and nasal obstruction (n = 12). Five presented with unilateral proptosis, one with meningitis, one with epilepsy, two with SAH, and one patient presented with trigeminal neuralgia. Craniotomy alone was chosen for the patients with isolated sphenoiditis (n = 2) while a combined cranial and endonasal approach was elected for the other patients (n = 10). Adjuvant antifungal therapy was used for 3-12 months. Patients were followed up clinically and radiologically for an average 36-month period (range = 12-50 months) with disease eradication achieved in eight patients (67%). Two died as consequence to SAH. Follow up also showed that three patients (25%) had sinunasal recurrence requiring evacuation through an endonasal approach. Conclusions: Surgical intervention, with adjuvant antifungal therapy, aiming for safe total removal of the fungal burden, whenever feasible, has a major role in the management of invasive sinonasal aspergillosis with orbitocranial extension with minimal morbidity and good outcomes.
Keywords: Fungal brain abscess; invasive aspergillus sinusitis; intracranial fungal granuloma; isolated sphenoiditis; mycotic fungal cerebral aneurysm